CHI '14 Extended Abstracts on Human Factors in Computing Systems 2014
DOI: 10.1145/2559206.2581291
|View full text |Cite
|
Sign up to set email alerts
|

Performance of modern gaming input devices in first-person shooter target acquisition

Abstract: We present a pilot study quantifying the targeting performance of several modern game input devices. These included a mouse, a game controller, the PS Move and the Kinect. Our study used a 3D first-person shooting game task, based on the ISO 9241-9 experimental paradigm for evaluating pointing devices. Comparison of performance measures indicated that the mouse was best, with the game controller coming in a close second. Performance of the 3D input devices (Move and Kinect) was much worse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 8 publications
(19 reference statements)
1
9
0
4
Order By: Relevance
“…The travel task used these functions most intensely, and control schemes that used the mouse had the highest scores. The preference for mouse input perhaps not surprising, given that prior research that also found mouse input to be faster and more accurate than HMD input [43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The travel task used these functions most intensely, and control schemes that used the mouse had the highest scores. The preference for mouse input perhaps not surprising, given that prior research that also found mouse input to be faster and more accurate than HMD input [43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Given that control schemes were the focus of our study, we avoided introducing another layer of novelty by using non-standard controllers. Mouse and keyboard have the additional advantages of increased accuracy and speed as compared to other input devices such as gamepads, wands, gesture and positional tracking [43][44][45][46].…”
Section: Equipmentmentioning
confidence: 99%
“…A comparative analysis of modern gaming input devices is available at [16]: users were asked to perform a shooting task and performance measurements with four devices. Results show that the mouse is still the best tool, while the game controller remains in a close second position.…”
Section: State Of the Artmentioning
confidence: 99%
“…Simulation and analysis of 3D Fitts' testing has highlighted increased performance of mice and traditional console controllers over open-gesture capture devices (such as the Microsoft Kinect and Sony Move). These devices were also shown to require a heightened spatial awareness than that of the traditional mouse and controller interface (Zaranek, 2014) and were therefore not considered for our experiment. Here, we have concerned ourselves with the 3D application of control in in-game environments, which also requires consideration of the zero-and first-system ordering of sensor modalities that are distributed between the left and right effectors of the body.…”
mentioning
confidence: 99%